2017
DOI: 10.1186/s12981-017-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

High level of HIV-1 drug resistance mutations in patients with unsuppressed viral loads in rural northern South Africa

Abstract: BackgroundCombination antiretroviral therapy (cART) has significantly reduced HIV morbidity and mortality in both developed and developing countries. However, the sustainability of cART may be compromised by the emergence of viral drug resistance mutations (DRM) and the cellular persistence of proviruses carrying these DRM. This is potentially a more serious problem in resource limited settings.MethodsDRM were evaluated in individuals with unsuppressed viral loads after first or multiple lines of cART at two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
4
24
0
1
Order By: Relevance
“…As a result, even before the restricted availability of etravirine in Zambia, more than one out of three (36%) patients with HIVDR may potentially be resistant to the only salvage NNRTI available in the public health sector in Zambia. The high prevalence of the Y181C and Y188C mutations has been demonstrated in earlier studies from the region including Zambia [9,26,11]. In our study, resistance to these drugs may be due in part to cross resistance with nevirapine and efavirenz which are widely used in PMTCT or first line ART.…”
Section: Plos Onesupporting
confidence: 66%
See 1 more Smart Citation
“…As a result, even before the restricted availability of etravirine in Zambia, more than one out of three (36%) patients with HIVDR may potentially be resistant to the only salvage NNRTI available in the public health sector in Zambia. The high prevalence of the Y181C and Y188C mutations has been demonstrated in earlier studies from the region including Zambia [9,26,11]. In our study, resistance to these drugs may be due in part to cross resistance with nevirapine and efavirenz which are widely used in PMTCT or first line ART.…”
Section: Plos Onesupporting
confidence: 66%
“…High levels of HIVDR mutations are not unique to AYA or Zambia. Several studies among adults from Zambia, South Africa, Togo and Tanzania, have shown a range of HIVDR from 84-98% [26,27]. The only study among children and adolescents conducted in Tanzania, found 90% had drug resistance with 79% having multiclass resistance.…”
Section: Plos Onementioning
confidence: 99%
“…The prevalence of RPV-resistant isolates ranges from 4 to 10% in individuals who are treatment naive (26)(27)(28)(29)(30)(31)(32)(33) to 42 to 72% in individuals with viremia during non-RPVcontaining ART (34)(35)(36)(37)(38)(39)(40)(41). Three clinical studies evaluated the efficacy of RPV-containing regimens compared to EFV-containing regimens in treatment-naive individuals (the ECHO, THRIVE, and STaR trials), all of which identified multiple RPV-associated resistance mutations that arose in subjects on RPV-containing ART (42,43).…”
mentioning
confidence: 99%
“…Thus, special attention in addition to strengthening therapeutic education must be paid to patients who replicate between 50 and 1000 copies to minimize the occurrence of mutations. This is even more true since a lot of scientific evidence has shown in so-called controlled patients with persistent viral replication, a higher risk of occurrence of therapeutic failure [16] [17] [18] [19]. Virological failure in our series was 19%.…”
Section: Discussionmentioning
confidence: 58%